GOD AND MAN IN JOHN DONNE'S AND GERARD MANLEY HOPKINS'S SONNENTS - Konoplyuk, N.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
J. Donne's and G.M. Hopkins's religious and metaphysical lyrics can be considered within the common intertextual context. The article studies two sonnets: "As due by many titles I resign" from "Holy Sonnets" by J. Donne and "Thou art indeed just, Lord, if I contend" from "Terrible Sonnets" by G.M. Hopkins. The aim of the study is to identify similarities and differences in the interpretation of the images of God and Man in Donne's and Hopkins's religious lyrics. Both J. Donne "Holy Sonnets" and G.M. Hopkins's "Terrible Sonnets" are based on the deep emotional distress of the authors whose religious beliefs suffered dramatic transformation in the course of life. Crisis of ideals brought both poets to the point when a man is forces to seek answers to his questions. Neither sonnet sequence was intended for publication so both of them were first edited posthumously. In both poems, the lyrical hero appeals to God using similar address forms emphasizing the subordinate position of the narrator. God's image is constructed by both poets according to the Christian tradition. Donne's image of the lyrical hero is connected with the ideas of decay and betrayal. Hopkins's hero is personalized and his questions for God sound more rebellious. Traditional dichotomy in the sonnets composition reveals the emotional development in them. In Donne's poem, the emotional explosion denotes the turn from the octave to the sestet. However, in Hopkins's sonnet, the sestet is marked by the increasing feeling of despair.